A Recent Review On: Effect of Nutrients On Brain Function and Development - Liaqat, Sundas; Bibi, Farida; Anjum, Zahin; Azeem, Jauhar; Ambreen, Sadaf; Bibi, Ayesha (Indus Journal of Bioscience Research, 2025)
Recent studies have demonstrated the important role that nutrition plays in maintaining cognitive health by highlighting the substantial effects of different nutrients on brain growth and function. Research articles from Google scholar, scihub, PUBMED was searched for food and nutrients for brain development and function. Important nutrients that are connected to neurodevelopment, synaptic plasticity, and general cognitive function include omega-3 fatty acids, B vitamins, antioxidants, and vital minerals. The structure and function of the brain depend on omega-3 fatty acids, especially DHA, and neurotransmitter production and cognitive resilience are supported by B vitamins. Vitamins E and C are examples of antioxidants that reduce oxidative stress and support the health of neurons. Cognitive deficits are linked to mineral shortages, especially those involving iron and zinc. This review summarizes research on the relationship between long-term cognitive problems and nutritional deficiencies, particularly during important developmental stages. Additionally, diets high in particular nutrients are linked to better mental health outcomes and lowers risks of various illnesses caused by neurodegeneration. Overall, this review highlights how crucial a balanced diet is for promoting brain health throughout life.